Dubki - Radimov, Tatyana Pavlovna (Советский художник (Soviet Artist), 1952)
Artwork ; Forest of oak trees 1952 reproduction of 1948 painting 'Dubki' ('Oak') by Russian artist T. P. Radimov. Original title: Дубки PO-1184